The Correlation between Conflict Management Styles and Nurse Managers\' Demographic Characteristics in Hamadan Therapeutic and Educational Centers - Ali Bikmoradi; Fatemeh Abdi; Alireza Soltanian; Yadollah Hamidi (Hamadan University of Medical Sciences, 2017)
Introduction: Presence of conflict seems inevitable in organizations, especially in therapeutic and educational centers, considering the variety of personnel, patients, and their families' education and cultures. Nurse managers could effectively be involved in conflict management at these therapeutic and educational centers. This study aimed at assessing nurse managers' conflict management strategies at Hamadan therapeutic and educational centers. Methods: A correlation descriptive study was conducted by Putnam and Wilson's conflict management questionnaire on 400 nurse managers of Hamadan therapeutic and educational centers. Data were analyzed by SPSS (Version 16) via Pierson correlation coefficient, t test and Analysis of Variance (ANOVA). Results: Overall, 52.2% of nurse managers used problem solving (collaboration and accommodation), 37.8% used none-confrontational strategies (avoidance and compromising) and 3% employed control (competing) styles for conflict management at Hamadan therapeutic and educational centers. There was a significant correlation between their conflict management strategies and age, marital status, work experience, managerial work experience, and employment status (P < 0.05). Conclusions: There were direct and significant correlations between nurse managers' conflict management styles and some of their demographic characteristics. Therefore, it is important to consider demographic characteristics before the selection of managers. Conflict management education could improve nurse managers' capabilities for conflict management at Hamadan therapeutic and educational centers